New media, new literacies and redefinition of learning spaces and communities (2018)
New media gave birth to new literacies and new literacies redefined space and communities. Although the contemporary society has more learning spaces and close communities yet persons still suffer from those problems that were thought would go into extinction. While no one can reverse the trend and influence of the new media, humanity should exercise caution for the preservation of its values.